Greece 2020: Designing a Road Map for Development - Katseli, Louka T. (Études helléniques / Hellenic Studies, 2006)
Greece could become a major European hub for services in the wider region in the years to come. Signalling a road map for development in such a direction could become a major driver for consensus-building around a national reform agenda that does not appear feasible under present conditions. Such undertaking requires both solid analysis of likely changes in the global, European and regional environment as well as evaluation of domestic preferences, capabilities and options. More importantly, it requires political leadership that would ensure policy coherence for development and effective mobilization of all relevant stakeholders.